Patency trials with reteplase (r-PA): what do they tell us? - Bode, Christoph; Nordt, Thomas K.; Peter, Karlheinz; Smalling, Richard W; Runge, Marschall S; Kübler, Wolfgang (The American journal of cardiology, 1996)
Thrombolytic therapy has been shown to reduce mortality and morbidity after acute myocardial infarction. Therapeutic benefit seems to be directly correlated with completeness of reperfusion (Thrombolysis in Myocardial Infarction [TIMI] grade 3 flow) of the infarct-related coronary artery, as well as the timeliness of reperfusion. To determine which regimen of reteplase (r-PA), a deletion mutant of wild-type tissue plasminogen activator (t-PA), is most effective for clinical thrombolysis, several reteplase regimens were compared with the most successful standard regimens of recombinant t-PA (alteplase) in 2 large-scale, randomized studies. All patients received aspirin and intravenous heparin. In the Reteplase Angiographic Phase II International Dose Finding Trial (RAPID-1), results in 606 randomized patients showed that a 10 + 10 U double bolus of reteplase was more effective than a 15 U single bolus, a 10 + 5 double bolus, or conventional alteplase (100 mg over 3 hours). In the Reteplase versus Alteplase Patency Investigation During Acute Myocardial Infarction (RAPID-2) trial, results in 324 patients showed that significantly more patients achieved patency of the infarct-related artery (TIMI grade 2 or 3 flow) at 90 minutes with reteplase (10 + 10 U double bolus) than with accelerated alteplase (100 mg over 90 minutes): 83.4% versus 73.3%, respectively (p = 0.03). The incidence of complete patency (TIMI grade 3 flow) at 90 minutes was likewise greater with reteplase than with accelerated alteplase (59.9% vs 45.2%, respectively; p = 0.01). At 60 minutes, the incidence of TIMI grade 2 or 3 flow was also significantly higher with reteplase than with alteplase (81.8% vs 66.1%, respectively; p = 0.01), as was the incidence of TIMI grade 3 flow (51.2% vs 37.4%, respectively; p <0.031). The 35-day mortality rate was 4.1% for reteplase and 8.4% for alteplase (p = not significant). Reteplase and alteplase did not differ significantly with regard to the occurrence of severe bleeding (12.4% vs 9.7%, respectively) or hemorrhagic stroke (1.2% vs 1.9%, respectively). The results of these trials show that reteplase, given as a 10 + 10 U double bolus, achieves significantly higher rates of early reperfusion of the infarct-related coronary artery and is associated with significantly fewer acute coronary interventions when compared with front-loaded alteplase. The benefits of reteplase are achieved without any apparent increased risk of complications. © 1996 by Excerpta Medica, Inc. Am J Cardiol 1996;78(suppl 12A):16-19